Penerapan Combined Compromise Solution (CoCoSo) Method Dalam Sistem Pendukung Keputusan Pemilihan Modem - Very Hendra Saputra; Temi Ardiansah (PT. SNN MEDIA TECH PRESS, 2022)
The choice of modem is an important decision in accessing the internet, because a modem is a key device that connects a computer device or network to internet services. The Combined Compromise Solution (CoCoSo) method is an approach used in multi-criteria decision making to balance various factors related to a problem. This study aims to apply the Combined Compromise Solution method in modem selection so that users get a modem that meets their needs well, provides a stable and fast internet connection. The results of alternative ranking using the Combined Compromise Solution (CoCoSo) method gave the results of Rank 1, namely the MQ531 Modem with a final value of 6.3689, Rank 2, namely the Huawei E5577 Max Modem with a final value of 6.3689, Rank 3, namely the Telkomsel Orbit Star A1 Modem with a final value of 5.8796.